Remittances and Inequality: A Dynamic Migration Model - Frédéric Docquier; Hillel Rapoport (Institute for the Study of Labor (IZA), 2003)
We develop a model of the interdependencies between migration, remittances and inequality, and investigate how migration and subsequent remittances affect inter-household inequality in the origin communities. An important feature of our model is that we take into account the impact of migration on the local (rural) labor market. Migration is shown to decrease wealth inequality but may generate higher income inequality. Moreover, the short-run and long-run impacts of migration on income inequality may also be of opposite signs, suggesting that the dynamic relationship between migration and inequality may well be characterized by an inverse U-shaped pattern. This is consistent with the findings of the empirical literature on remittances and inequality, but offers a different interpretation, with no need to endogenize migration costs through the role of migrant networks.
Keywords: D31; J61; O15; O11; 330; migration; remittances; inequality; Gastarbeiterüberweisung; Einkommensverteilung; Haushaltsökonomik; Migrationstheorie; Dualökonomie; Theorie